Exposure to environmental tobacco smoke in the workplace in Macedonia: where are we now? - Jordan Minov; Jovanka Karadzinska-Bislimovska; Kristin Vasilevska; Risteska-Kuc, Snezana; Saso Stoleski (Walter de Gruyter GmbH, 2008)
To assess the prevalence and the level of exposure to environmental tobacco smoke (ETS) in the workplace after the enactment of the law restricting indoor smoking in Macedonia, we performed a cross-sectional, self-administered questionnaire study including 372 never-smoking workers recruited from six workplaces. We found a high prevalence of workers exposed to ETS in the workplace (27.4 %) with no significant difference between particular occupation groups. We found no significant difference in the prevalence of passive smokers in the workplace between this study and our study conducted before the law was enacted (31.5 % vs. 27.4 %, P=0.324). The prevalence of workers exposed to ETS for less than three hours a day was significantly lower than of passive smokers with longer exposure (28.4 % vs. 71.6 %, P=0.038). The prevalence of workers exposed to ETS from less than 10 cigarettes smoked by coworkers per day was lower than the prevalence of workers with higher exposure, but statistical significance was not reached (37.9 % vs. 62.1 %, P=0.087). Our findings indicate a high prevalence and a high level of exposure to ETS in the workplace, which calls for stricter adherence to smoking-free legislation or even the total ban of smoking in the workplace.
Keywords: health effects; legislation; occupation; passive smoking; questionnaire